Probability-Based Design and Life Cycle Assessment of a Spun Concrete Pole - Štěpánek, Petr; Laníková, Ivana; Šimůnek, Petr (Atlantis Press, 2015)
This contribution compares concrete structure design results obtained via the partial reliability factor method and using a probability-based method. The Monte Carlo simulation method, modified by the Latin Hypercube Sampling method, was used to calculate the reliability of a designed structure. Economic and ecological aspects (acquisition costs, CO2 and SO2 emissions and embodied energy associated with the concrete member through the production, utilization and demolition stages of its life cycle) were taken into account when assessing the quality of the design. An example of a designed structure – a prestressed spun concrete pole manufactured from reinforced concrete – is presented.

This contribution compares concrete structure design results obtained via the partial reliability factor method and using a probability-based method. The Monte Carlo simulation method, modified by the Latin Hypercube Sampling method, was used to calculate the reliability of a designed structure. Economic and ecological aspects (acquisition costs, CO2 and SO2 emissions and embodied energy associated with the concrete member through the production, utilization and demolition stages of its life cycle) were taken into account when assessing the quality of the design. An example of a designed structure – a prestressed spun concrete pole manufactured from reinforced concrete – is presented.
Probability-Based Design and Life Cycle Assessment of a Spun Concrete Pole
Keywords: Concrete Structure; Reinforced Concrete; Probability Based Design; Environmental Aspects; Concrete Structure; Reinforced Concrete; Probability Based Design; Environmental Aspects